Psychological and Biological Changes Observed in The Mind of Patients with Alzheimer’s Disease - Narmetova Yulduzxan Karimovna; Abdizhamilova Zerzada Abdisalamovna (Scientific Trends, 2024)
Alzheimer’s disease (AD) is a progressive neurodegenerative disorder characterized by cognitive decline, memory impairment, and significant psychological changes, making it one of the most common causes of dementia in older adults. Affecting millions worldwide, AD poses a profound impact on both patients and their families. This paper explores the dual dimensions of Alzheimer’s disease: the biological changes in the brain and the psychological alterations experienced by patients. Biologically, AD is marked by the buildup of amyloid-beta plaques and tau protein tangles, leading to neuronal death and brain atrophy, particularly in regions responsible for memory and executive functions. These structural changes in the brain correlate with a gradual decline in mental faculties, manifested in memory loss, impaired judgment, and disorientation. Psychologically, Alzheimer’s patients undergo emotional and behavioral shifts that can include depression, anxiety, agitation, and hallucinations, affecting their overall quality of life and social relationships. These psychological changes often exacerbate as the disease progresses, transforming not only the patient’s cognitive state but also their personality and emotional well-being. Research has shown that biological changes in the brain contribute directly to these psychological symptoms, revealing a complex interplay between molecular and psychological processes. Advances in neuroimaging and biomarker studies have improved the understanding of AD pathology, yet effective treatments remain limited.
Keywords: Neurodegeneration, amyloid plaques, cognitive decline, brain atrophy, behavioral changes, dementia, biomarkers, emotional changes.